2005
DOI: 10.1063/1.1944230
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of CF4-plasma fluorinated HfO2 gate dielectrics with TaN metal gate

Abstract: Articles you may be interested inEffects of fluorine incorporation and forming gas annealing on high-k gated germanium metal-oxidesemiconductor with Ge O 2 surface passivation Appl. Phys. Lett. 93, 073504 (2008);In this paper, fluorine incorporation into the HfO 2 gate dielectrics by post CF 4 plasma treatment was proposed to improve the electrical characterization. TaN-HfO 2 -p-Si capacitors were demonstrated in this work. The characteristics of fluorinated HfO 2 gate dielectrics were improved, including the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 10 publications
0
27
0
Order By: Relevance
“…These traps and excess oxygen in the Al 2 O 3 blocking layer degrade the P/E properties and retention characteristic of flash memory devices. On the other hand, it is reported that fluorine treatment can improve the electrical properties and oxide reliability of high-k dielectric materials by reducing their defects [8,9]. To obtain ideal tunnel layer with SiO 2 /HfO 2 / SiO 2 dielectric stack, fluorine incorporation by fluorine ion implantation at different stages of processing has been fully researched [10].…”
Section: Introductionmentioning
confidence: 99%
“…These traps and excess oxygen in the Al 2 O 3 blocking layer degrade the P/E properties and retention characteristic of flash memory devices. On the other hand, it is reported that fluorine treatment can improve the electrical properties and oxide reliability of high-k dielectric materials by reducing their defects [8,9]. To obtain ideal tunnel layer with SiO 2 /HfO 2 / SiO 2 dielectric stack, fluorine incorporation by fluorine ion implantation at different stages of processing has been fully researched [10].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the bias temperature instability is related to the generation of interface traps and bulk traps [1]. It was known that fluorine incorporation in the SiO 2 gate dielectrics improves the electrical and reliability characteristics by replacing Si-H bonds with Si-F bonds [2]- [7]; however, an excess amount of fluorine incorporation increases oxide thickness. It is known that excessive fluorine annealing replaces Si-O bonds with Si-F bonds, which generates reactive oxygen atoms.…”
Section: Introductionmentioning
confidence: 99%
“…Terai et al reported that the incorporation of fluorine ions into the SiON/Si interface reduced the interface states and decreased the negative-bias temperature instability (NBTI) because of the high binding energy of the Si-F bond [5]. In our previous studies [6], [7], we were able to improve the electrical characteristics (e.g., hysteresis and breakdown voltage) and the reliability of both HfO 2 and Al 2 O 3 by fluorine incorporation. In this letter, we both reduced the NBTI degradation and improved the electrical characteristics of HfMoN/Gd 2 O 3 p-channel metal-oxide-semicondcuctor field-effect transistors (pMOSFETs) by fluorine-ion implantation.…”
Section: Introductionmentioning
confidence: 86%